2015
DOI: 10.1080/14786435.2015.1066939
|View full text |Cite
|
Sign up to set email alerts
|

Shape memory behavior in Fe3Al-modeling and experiments

Abstract: The Fe 3 Al alloy with D0 3 structure exhibits large recoverable strains due to reversible slips. Tension and compression experiments were conducted on single crystals of Fe 3 Al, and the onset of slip in forward and reverse directions were obtained utilizing high-resolution digital image correlation technique. The back stress provides the driving force for reversal of deformation upon unloading, resulting in a superelastic phenomenon as in shape memory alloys. Using density functional theory simulations, we o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 43 publications
0
11
0
Order By: Relevance
“…Recently, the present authors reported the CRSS values attained by the first principle, Density Functional Theory (DFT) calculations on DO 3 -Fe 3 Al. Fig.1(a), adopted from this aforementioned study, illustrates the asymmetry in <111> cross sections of  curves on planes exhibiting the break-down of Schmid Law [21]. This asymmetry is also reflected on the resolved shear stress vs shear strain curves in Fig.1(b).…”
Section: Introductionmentioning
confidence: 90%
See 4 more Smart Citations
“…Recently, the present authors reported the CRSS values attained by the first principle, Density Functional Theory (DFT) calculations on DO 3 -Fe 3 Al. Fig.1(a), adopted from this aforementioned study, illustrates the asymmetry in <111> cross sections of  curves on planes exhibiting the break-down of Schmid Law [21]. This asymmetry is also reflected on the resolved shear stress vs shear strain curves in Fig.1(b).…”
Section: Introductionmentioning
confidence: 90%
“…A stress concentrator was inserted inside the pristine crystal of DO 3 -Fe 3 Al as a straight dislocation source. In 8 order to evaluate the theoretical CRSS values on the glide plane, we utilized the modified P-N formalism [21]. This formalism relates Peierls stress to the gradient of the total energy of the system with respect to the position of the dislocation line.…”
Section: Molecular Dynamics (Md) Simulationsmentioning
confidence: 99%
See 3 more Smart Citations